Research trends in the use of augmented reality in science education: Content and bibliometric mapping analysis - Arici, Faruk; Yildirim, Pelin; Caliklar, Şeyma; Yilmaz, Rabia M. (Computers and education, 2019)
The aim of this study was to reveal research trends over the last six years by content analysis and to examine bibliometric results of articles related to the use of augmented reality (AR) in science education. For bibliometric mapping analysis, a total of 147 articles were accessed and for content analysis, a total of 79 articles published between 2013 and 2018 years were included from the Web of Science. From this, a total of 62 articles were selected for analysis. Our results revealed that mobile learning, science education, science learning and e-learning were the most used keywords in articles, while the focus of more recent articles tended to be on mobile learning. The results showed that recent articles have mostly focused on mobile learning and e-learning environments. The most-used words in the abstracts were education, knowledge, science education, experiment and effectiveness. It is evident that recent articles have focused mostly on students' knowledge and achievement. Azuma, Dunleavy and Klopfer are the most cited authors in this field. This is not surprising as they are probably the leading authors on AR in the literature. The most cited journals are Computers & Education, Journal of Science Education & Technology, Educational Technology and Society, Computers in Human Behavior, and British Journal of Educational Technology. These are the most prominent journals on the use of technology in education. Content analysis results showed that “Learning/Academic Achievement”, “Motivation” and “Attitude” have been the most examined variables in the articles. Since academic achievement is highly influenced by motivation and attitude, it is understandable that these variables are considered together in reviewed studies. It was found that mobile applications and marker-based materials on paper have been the most-favored types of materials for AR because these types of materials are easy to use and they can be developed easily and practically. Quantitative studies were the most used research design type but there have been only a limited number of qualitative studies in the last six years. This may be due to the increased tendency to use quantitative and mixed studies in recent years. •The most cited journal is Computers & Education in this field.•Augmented reality, mobile learning, and science education, are the most used keywords.•Mostly used words in abstracts are reality, education, knowledge and science education.•Academic achievement and motivation are the most examined variables.•Quantitative studies are the most used research design type.